Allogeneic plasma gel in II Degree Burn: A case report - Pedraza-La Barrera , Joan; Quispe-Villegas, Gustavo A.; Becerra-Gutiérrez, Lizzie Karen; Tello-Vera, Stalin (Acta Biomedica Atenei Parmensis, 2025)
Skin burns are injuries caused by physical and chemical mechanisms, with thermal burns from fire being the most common. These injuries can cause death or long-term disability; The use of orthobiological agents such as platelet-rich plasma and its derivatives have shown good results in chronic wounds and skin lesions.The present study presents the case of a 1 year 6-month-old child who suffered a second-degree thermal burn on the palm of his right hand, which caused him a lot of pain and was resistant to analgesics. For this reason, it was decided to perform a regenerative therapy based on debridement and application of 2 sessions of allogeneic plasma gel, from the mother, as a biofilm, in addition, topical antibiotic cream was added to cover the wound. After 8 days of the first application, the wound had re-epithelialized adequately, with almost no evidence of the previous burn, which allowed rapid rehabilitation and complete recovery. Allogeneic plasma gel could be a safe, low-cost and effective option for the healing of second-degree burns and an alternative to skin autografts or xenografts.